The Role of Initial Soil Conditions in Shallow Landslide Triggering: Insights from Physically Based Approaches. (2nd June 2019) - Schilirò, L.; Poueme Djueyep, G.; Esposito, C.; Scarascia Mugnozza, G.
Abstract : In the last years, the shallow landslide phenomenon has increasingly been investigated through physically based models, which try to extend over large-area simplified slope stability analyses using physical and mechanical parameters of the involved material. However, the parameterization of such models is usually challenging even at the slope scale, due to the numerous parameters involved in the failure mechanism. In particular, considering the scale of the phenomenon, the role of transient hydrology is essential. For this reason, in this work we present the outcome of different experimental tests conducted on a soil slope model with a sloping flume. The tested material was sampled on Monte Mario Hill (Rome, Central Italy), an area which has been frequently affected by rainfall-induced landslide events in the past. In this respect, we also performed a physically based numerical analysis at the field conditions, in order to evaluate the response of the terrain to a recent extreme rainfall event. The results of the flume tests show that, for the same material, two different triggering mechanisms (i.e., uprise of a temporary water table and advance of the wetting front) occur by varying the initial water content only. At the same time, the results of the numerical simulations indicate that clayey sand and lean clay are the soil types mostly influenced by the abovementioned rainfall event, since the initial moisture conditions enhance the formation of a wide wetting front within the soil profile.